Design and fabrication of golf ball picker - Mohd Raz Firdaus, Ramli (2008)
Basically golf ball picker is often used in golf field because it would help worker to pick up golf ball after player finished played. Introducing this design of golf ball picker directly help worker to make their job much easier and reasonable. In this project also content main part that important which is describe this design or this product would perform well. In this project also it was using valve mechanism in order to pick up ball from grass surface. The main part has been manufactured outside product so that it could be assemble easily and with this method also carry out benefit that we could get from there. Overall this project has been done and finished on schedule.